Black bodies, white gold : art, cotton, and commerce in the Atlantic World - Arabindan-Kesson, Anna (Durham : Duke University Press, 2021)
Frontmatter -- Contents -- Acknowledgments -- Illustrations -- Introduction -- 1 Circuits of Cotton -- 2 Market Aesthetics -- 3 Of Vision and Value -- 4 Material Histories and Speculative Conditions -- Coda -- Notes -- Bibliography -- Index
In Black Bodies, White Gold Anna Arabindan-Kesson uses cotton, a commodity central to the slave trade and colonialism, as a focus for new interpretations of the way art, commerce, and colonialism were intertwined in the nineteenth-century Atlantic world. In doing so, Arabindan-Kesson models an art historical approach that makes the histories of the Black diaspora central to nineteenth-century cultural production. She traces the emergence of a speculative vision that informs perceptions of Blackness in which artistic renderings of cotton-as both commodity and material-became inexorably tied to the monetary value of Black bodies. From the production and representation of "negro cloth"-the textile worn by enslaved plantation workers-to depictions of Black sharecroppers in photographs and paintings, Arabindan-Kesson demonstrates that visuality was the mechanism through which Blackness and cotton became equated as resources for extraction. In addition to interrogating the work of nineteenth-century artists, she engages with contemporary artists such as Hank Willis Thomas, Lubaina Himid, and Yinka Shonibare CBE RA, who contend with the commercial and imperial processes shaping constructions of Blackness and meanings of labor
Mode of access: Internet via World Wide Web.
In English
Keywords: Cotton growing -- History -- 19th century -- Atlantic Ocean Region; Cotton trade -- History -- 19th century -- Atlantic Ocean Region; Slavery -- History -- 19th century -- Atlantic Ocean Region; African diaspora in art; Cotton in art; Slavery in art; SOCIAL SCIENCE / Black Studies (Global).